Thermoanalytical study of the complexes of 4-dimetilaminocinnamylidenepiruvate with manganese (II), cobalt (II), nickel (II), cupper (II), zinc (II) and lead (II), in the solid state - SCHNITZLER, Egon; LAZZAROTTO, Márcio; CARVALHO-FILHO, Marco Aurelio da Silva; Ionashiro, Massao [UNESP] (Editora Unesp, 2002)
Os compostos dos 4-dimetilaminocinamalpyruvatos (4-DMCP) de Mn (II), Co (II), Ni (II), Cu (II), Zn (II) e Pb (II) foram preparados. Estes compostos foram estudados pelas técnicas termoanaliticas: termogravimetria (TG), termogravimetria derivada (DTG), calorimetria exploratória diferencial (DSC), difratometria de raios - X pelo método do pó e titulação complexométrica com EDTA. Através dos resultados obtidos pela titulação complexométrica com EDTA, TG, DTG e DSC foi possível estabelecer o grau de hidratação, estequiometria e estabilidade térmica dos compostos preparados.

Solid state compounds M-4-DMCP, where 4-DMCP is 4-dimethylaminocinnamylidenepyruvate and M represents Mn (II), Co (II), Ni (II), Cu (II), Zn (II) and Pb (II) were prepared. These compounds were studied by thermoanalitycal techniques: thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometric titration with EDTA. From the results obtained by the complexometric titration with EDTA, TG, DTG and DSC curves, was possible to establish the hydration degree, stoichiometry and thermal stability of the prepared compounds.
Estudo termoanalítico dos complexos 4-dimetilaminocinamalpiruvatos (4-DMCP) de manganês(II), cobalto(II), níquel(II), cobre(II), zinco(II) e de chumbo(II), no estado sólido
Keywords: 4-dimetilaminocinamalpiruvato; análise térmica; TG; DSC; 4-dimethylaminocynnamylidenepyruvate; thermal analysis; TG; DSC